2015
DOI: 10.17795/zjrms1105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Selenite on Lipid Peroxidation and Glutathione in Alloxan Induced Diabetic Rats

Abstract: Background: Diabetes-related dysfunctions are the major causes of mortality and morbidity for diabetic patients. Objectives: Selenium is a potent antioxidant. In the present study, we examined antioxidative activities of sodium selenite and possible protective effect of it on serum, liver and kidney lipid peroxidation and glutathione in alloxan-induced type 1 diabetic rats. Materials and Methods: In this experimental study 40 Sprage Dawley male rats were divided into 4 groups randomly; group I as control, grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…These results indicated that the treatment with sodium selenite led to attenuate the effect of ACR on rats. In harmony with this finding, Ahmadvand and Khosrowbeygi (2015) had indicated that the decrease in MDA values is an indicator of the ability of the sodium selenite solution to reduce the rate of fat oxidation. However, in G4 significant differences still could be noticed in all tested parameters compared to G1.…”
Section: Antioxidant Parameters In Blood Serummentioning
confidence: 82%
“…These results indicated that the treatment with sodium selenite led to attenuate the effect of ACR on rats. In harmony with this finding, Ahmadvand and Khosrowbeygi (2015) had indicated that the decrease in MDA values is an indicator of the ability of the sodium selenite solution to reduce the rate of fat oxidation. However, in G4 significant differences still could be noticed in all tested parameters compared to G1.…”
Section: Antioxidant Parameters In Blood Serummentioning
confidence: 82%
“…Stem cells are cells that can retain prolonged self-renewal ability and can differentiate into numerous tissue types [9]. There are different sources of stem cells such as embryonic stem cells, induced pluripotent stem cells, bone marrow stem cells (BMSCs) and adipose-derived stem cells (ASCs) [10].…”
Section: Stem Cells Application In Wound Healingmentioning
confidence: 99%
“…Humans are exposed to this metal from numerous sources; contaminated air, water, soil, and food [1] . Selenium and flavonoids have been shown to alleviate heavy metal toxicity [9,14] . Therefore, the present study aimed to evaluate the possible mitigating effect of selenite, and some flavonoids (morin, naringin and hesperetin) against acute HgCl 2 toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…A total number of 70 adult male albino rats were randomly divided into 10 groups (n=7/group) as follows: a control group (group 1), groups 2 and 6 were orally administered with 5 mg/kg body weight of either sodium selenite or HgCl 2 , respectively [9,10] . Groups 3, 4, and 5 were orally treated with 50 mg/kg body weight of morin, naringin, or hesperetin, respectively [11][12][13] .…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation